Sea Surface Temperature Trends (1993–2022) at the Central–West Java Border: Climate Change Indicator - Amir Yuliardi; Sugeng Hartono; Luhur Moekti Prayogo; Agung Tri Nugroho; Diah Ayu Rahmalia; Ratna Juita Sari (Yayasan Ekologi Masyarakat dan Sains, 2025)
This study analyzes the variability of sea surface temperature (SST) in the coastal waters of Cilacap and Pangandaran, South Java Sea, during the 1993–2022 period using satellite data from Marine Copernicus. The analysis covers long-term trends, interannual fluctuations, and seasonal patterns related to regional oceanographic dynamics such as ENSO and seasonal upwelling. The results show a warming trend of SST at 0.06 ± 0.02 °C per decade, indicating the influence of regional climate change. Interannual variability highlights significant cooling in 1997 (La Niña) and extreme warming in 1998 and 2010 (El Niño). Seasonal patterns reveal the highest SST from March to May during the west monsoon, and the lowest SST in August–September due to upwelling. Upwelling plays an important role in regulating sea temperatures and supporting biological productivity. These findings underscore the importance of SST monitoring for climate-adaptive marine resource management in the southern coastal region of Java.